2020
DOI: 10.1136/bmjopen-2019-032851
|View full text |Cite
|
Sign up to set email alerts
|

Reducing medicine-induced deterioration and adverse reactions (ReMInDAR) trial: study protocol for a randomised controlled trial in residential aged-care facilities assessing frailty as the primary outcome

Abstract: IntroductionMany medicines have adverse effects which are difficult to detect and frequently go unrecognised. Pharmacist monitoring of changes in signs and symptoms of these adverse effects, which we describe as medicine-induced deterioration, may reduce the risk of developing frailty. The aim of this trial is to determine the effectiveness of a 12-month pharmacist service compared with usual care in reducing medicine-induced deterioration, frailty and adverse reactions in older people living in aged-care faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The intervention occurred between August 2018 and June 2020 ( Supplement 1 , Supplementary data are available in Age and Ageing online). Approvals were obtained from four ethics committees ( Supplement 2 , Supplementary data are available in Age and Ageing online) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention occurred between August 2018 and June 2020 ( Supplement 1 , Supplementary data are available in Age and Ageing online). Approvals were obtained from four ethics committees ( Supplement 2 , Supplementary data are available in Age and Ageing online) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Four or more medicines has been chosen because evidence has demonstrated that gait and cognition may be impaired when a person is taking 5 or more medicines [ 30 ]. Residents were excluded if they were frail (≥0.40 on the Frailty Index) [ 27 ], had moderate or severe dementia (Psychogeriatric Assessment Scales <12/21 [ 31 ] or Montreal Cognitive Assessment MoCA ≤17/30) [ 32 ] or were receiving palliative or respite care [ 29 ]. Our study adopted an ‘opt out’ approach which meant that residents needed to have the capacity to decline participation if they wish to do so.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a limitation of the current study is the cross-sectional design, that only allows us to assess associations between dynamic gait parameters and the DBI. Future studies should focus on monitoring changes over time in dynamic gait parameters to examine medication-induced deterioration and adverse reactions [36].…”
Section: Discussionmentioning
confidence: 99%
“…75 Reducing Medicine Induced Deterioration and Adverse Reactions (ReMInDAR) trial: The trial aimed to determine the effectiveness of a pharmacist service in reducing medicine-induced deterioration, frailty and adverse reactions in older people living in aged-care facilities. 76 Early detection and management of cardiovascular disease risk factors (CVD) trial: The trial aimed to evaluate health checks to detect, diagnose and enable early intervention of cardiovascular disease. The service was delivered by community pharmacists in collaboration with general practice and other providers to ensure individuals with elevated risk status were offered appropriate treatment to reduce their overall risk and improve quality of care.…”
Section: Pharmacy Trial Programsmentioning
confidence: 99%